Introduction to plasmid biology - Clewell, Don (Henry Stewart Talks, 2008)
Ubiquity of plasmids, The prokaryotic world, Conjugation, Common traits encoded by plasmids, Conformation, Maintenance, Classification, Higher systems
Reviewed at 2023/04/16